Genetic pain loss disorders - Lischka, Annette; Lassuthova, Petra; Çakar, Arman; Record, Christopher J; Van Lent, Jonas; Baets, Jonathan; Dohrn, Maike F; Senderek, Jan; Lampert, Angelika; Bennett, David L; Wood, John N; Timmerman, Vincent; et al. (Nature reviews. Disease primers, 2022)
Genetic pain loss includes congenital insensitivity to pain (CIP), hereditary sensory neuropathies and, if autonomic nerves are involved, hereditary sensory and autonomic neuropathy (HSAN). This heterogeneous group of disorders highlights the essential role of nociception in protecting against tissue damage. Patients with genetic pain loss have recurrent injuries, burns and poorly healing wounds as disease hallmarks. CIP and HSAN are caused by pathogenic genetic variants in >20 genes that lead to developmental defects, neurodegeneration or altered neuronal excitability of peripheral damage-sensing neurons. These genetic variants lead to hyperactivity of sodium channels, disturbed haem metabolism, altered clathrin-mediated transport and impaired gene regulatory mechanisms affecting epigenetic marks, long non-coding RNAs and repetitive elements. Therapies for pain loss disorders are mainly symptomatic but the first targeted therapies are being tested. Conversely, chronic pain remains one of the greatest unresolved medical challenges, and the genes and mechanisms associated with pain loss offer new targets for analgesics. Given the progress that has been made, the coming years are promising both in terms of targeted treatments for pain loss disorders and the development of innovative pain medicines based on knowledge of these genetic diseases.
Keywords: kanálopatie; Hereditary Sensory and Autonomic Neuropathies; Pain Insensitivity, Congenital; Humans; lidé; Pain; dědičné senzorické a autonomní neuropatie; Channelopathies; bolest; kongenitální analgezie